Peninggalan Kesultanan Langkat Dalam Perkembangan Pendidikan Islam Di Tanjung Pura - Zakaria, Muhammad Saleh, Ahmad Fuadi (Pusdikra Publishing, 2023)
Sultan Tengku Abdul Aziz Jalil Rahmadsyah Al-Hajj carries a modern education which is full of logic and rationality and then juxtaposes it with a strong ethical and aesthetic based tradition. Sui-generis of modern and traditional education which places the value of modernity on the one hand and traditionality on the other, will synergize with each other to become alternative knowledge that is rich in perspective but is timeless from the spirituality that is its root. Azizi Mosque which is a historic building inherited from the Sultanate of Langkat, North Sumatra. The mosque which was founded by the Langkat sultanate still has ornaments and carvings on the original building design since 1902. This is an attraction to enjoy the splendor of the mosque which has cultural values ??of the Malay tribe. The Azizi Mosque is located at the Medan - Aceh road crossing, to be precise, in Tanjung Pura District, Langkat Regency. The Azizi Mosque is a witness to the history of the spread of Islam in the Malay lands. Even though it has been 120 years since its establishment in 1902, the Azizi Mosque building is still sturdy and majestic. Dominated by a very thick yellow color, Masid Azizi has elements of Malay culture and there are also various ornaments in the form of carvings on the windows, domes and even the minarets of the mosque which are influenced by Persian, Indian, Arabic and Turkish cultures, adding to the grandeur of the Azizi Mosque. Not only the ornaments, but the walls are also decorated with Koranic, geometrical and floral calligraphy which makes this historic building beautiful. Apart from being a witness to the spread of Islam in Malay lands, the Azizi Mosque during the Langkat Sultanate was used as a court and palace mosque. Islamic education is different from other education. Islamic education prioritizes Islamic values ??and is focused on the formation of human beings who have good morals and are obedient and subservient to Allah alone. Meanwhile, non-Islamic education does not place too much priority on Islamic elements and values, the only priority being the fulfillment of sensory needs. There were three main buildings as educational institutions at that time, including the Maslurah Madrasa which was founded in 1912, the Aziziah Madrasa in 1914 and the Mahmudiyah Madrasa in 1921. The three educational institutions were then named the Jama'iyah Mahmudiyah college. In 1923 to improve the quality of education at the Jama'iyah Mahmudiyah college, most of the teaching staff were teachers who had studied in the Middle East such as Mecca, Medina and Egypt.